2010
DOI: 10.1002/jbm.b.31684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica coating combined to a MDP‐based primer on the resin bond to Y‐TZP ceramic

Abstract: The aim of this study was to evaluate the influence of silica coating and 10-methacryloyloxydecyl dihydrogen phosphate (MDP)-based primer applications upon the bonding durability of a MDP-based resin cement to a yttrium stabilized tetragonal zirconia (Y-TZP) ceramic. Ninety-six Y-TZP tabs were embedded in an acrylic resin (free surface for adhesion: 5 × 5 mm(2)), ground finished and randomly divided into four groups (N = 24) according to the ceramic surface conditioning: (1) cleaning with isopropanol (ALC); (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 30 publications
(52 reference statements)
3
58
0
7
Order By: Relevance
“…Sandblasting with 30-µm silica-coated alumina showed similar results as Al 2O3. In all surface treatment groups, luting with MDPcontaining resin cement yielded higher SBS than with Bis-GMA-containing resin cement groups. This result agreed with the results of previous studies which reported higher bond strengths with the use of MDPbased primer 8,42) . This could be due to the capability of acidic functional monomer MDP reacting with the substrate [13][14][15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
“…Sandblasting with 30-µm silica-coated alumina showed similar results as Al 2O3. In all surface treatment groups, luting with MDPcontaining resin cement yielded higher SBS than with Bis-GMA-containing resin cement groups. This result agreed with the results of previous studies which reported higher bond strengths with the use of MDPbased primer 8,42) . This could be due to the capability of acidic functional monomer MDP reacting with the substrate [13][14][15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
“…The reason for this may be the MDP content of CSA cement, which enables bonding to silicate ceramic and the ceramic part of polymer infiltrated ceramic. The MDP-monomer, with its phosphate ester group, binds directly to surface oxides, and its methacrylate group enables copolymerization with the resin matrix of the luting cement 14) . Silane coupling agents provided considerable bond strength both on SC and VE, since silicate surfaces such as SC or VE allow for covalent Si-O-Si bonds between ceramic and silane coupling molecules.…”
Section: Shear Bond Strength To Polished Substratesmentioning
confidence: 99%
“…Thus, several surface conditioning methods have been suggested to condition zirconia surfaces physically and/or chemically where physico-chemical conditioning methods remain to be the best methods to increase adhesion of resin-based materials to zirconia [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, silica particles have been introduced that are readily silanized, eliminating the silanization process, thereby also reducing the chairside procedures. It is not known to date whether such particles could substitute available abrasives used in conjunction with 5 chairside air-abrasion procedures and exclude the additional application of silane coupling agents.…”
Section: Introductionmentioning
confidence: 99%